Cambrian suspension-feeding tubicolous hemichordates. Issue 1 (December 2016) - Nanglu, Karma; Caron, Jean-Bernard; Conway Morris, Simon; Cameron, Christopher
Abstract Background The combination of a meager fossil record of vermiform enteropneusts and their disparity with the tubicolous pterobranchs renders early hemichordate evolution conjectural. The middle CambrianOesia disjuncta from the Burgess Shale has been compared to annelids, tunicates and chaetognaths, but on the basis of abundant new material is now identified as a primitive hemichordate. Results Notable features include a facultative tubicolous habit, a posterior grasping structure and an extensive pharynx. These characters, along with the spirally arranged openings in the associated organic tube (previously assigned to the green algaMargaretia ), confirmOesia as a tiered suspension feeder. Conclusions Increasing predation pressure was probably one of the main causes of a transition to the infauna. In crown group enteropneusts this was accompanied by a loss of the tube and reduction in gill bars, with a corresponding shift to deposit feeding. The posterior grasping structure may represent an ancestral precursor to the pterobranch stolon, so facilitating their colonial lifestyle. The focus on suspension feeding as a primary mode of life amongst the basal hemichordates adds further evidence to the hypothesis that suspension feeding is the ancestral state for the major clade Deuterostomia.